Cementing Partnerships: Applying a Network-Mapping Tool in Tajikistan - Muhamedjonova, Nazira R.; Watkins, Jonathan; Nazarova, Sayora I.; Holding, P. A. (Frontiers in Public Health, 2021)
Background This article describes the integration of an innovative network-mapping tool within a monitoring, evaluation and learning system. We describe how it serves to strengthen vulnerable families to care for their children. We discuss the use of this tool as part of the process of measurement for change in the preparation for the sustainable scaling of programme implementation. Tajikistan has a legacy of soviet-style institutional care of children. Traditionally, very young children separated from their families have been cared for in institutional baby homes. This research is part of a wider project to transform these baby homes into community-oriented Family and Child Support Centres. Methods We mapped the networks of child support experienced by parents and service providers. We used interactive, semi-structured interviews, and the tool evolved through an iterative process. We generated data to describe the connections between children, families, professionals and supporting organisations. The resulting information revealed strengths and weaknesses in support provided, as well as perceptions of the quality of the support. Results The data showed that the main support for children comes from within their immediate household, but, over time, more distal support gained value. Variation in the networks of support related to gender, specific subgroups of need and location. Gender was the most influential determinant of patterns of support. Mothers’ knowledge of service provision, represented by a greater number and variety of contacts on their network-maps, was more diverse than fathers’. In contrast, fathers’ more limited networks showed connections to individuals and organisations with potentially more powerful decision-making roles. Conclusions Network-mapping is a valuable and adaptable tool that feeds into monitoring and evaluation at multiple levels. The process reveals the nature and extent of relationships of support for childcare and protection. It exposes the changes in these networks over time. Both the information provided and the process of collection can enrich care plans, create links within the network and inform decision-making that improves efficacy of delivery as we move to scale.